Analisis Strategi Pengembangan Kepariwisataan Sejarah di Kota Medan Dengan Metode SOAR (Studi Kasus Museum Negeri Provinsi Sumatera Utara) - Dayantri, Dayantri; Ramadhani, Sri; Syahbudi, Muhammad (Universitas Labuhanbatu, 2024)
This study aims to analyze the development strategy undertaken by the State Museum of North Sumatra province as one of the historical tourism in order to increase the value of PAD (local revenue) by increasing the number of visitors. This study uses qualitative methods with data analysis techniques using the SOAR method (strengths, Opportunities, Aspirations, Results).Data collection techniques used in the form of observation, interviews, questionnaires and documentation. The results of this study are: (1) the application of SOAR analysis at the State Museum of North Sumatra using internal and external factors analysis strategy. (2) calculation results on the comparison between strengths and weaknesses in the table IFAs and EFAS, IFAS calculation shows that Strenght (S) is greater than Opportunity (O). While EFAS calculation shows Results (R) is greater than Aspirations (a). (3) the results of the IE (Internal - external) matrix of the State Museum of North Sumatra province are located in Cell Number 1, namely concentration through vertical integration which indicates that the museum is in a strong state. And the results of SOAR obtained are in Quadrant II, a position that indicates a strong organization, but faces great challenges. (4) from the analysis that has been done, the State Museum of North Sumatra province is recommended to implement a diversification strategy by optimizing strengths to achieve measurable results.